2021
DOI: 10.36519/idcm.2021.61
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Adult and Pediatric COVID-19 Patients

Abstract: Objective: We aimed to describe the infectivity of adult and pediatric COVID-19 patients in the presence of viral shedding and anti-SARS-CoV-2 antibody response. Materials and Methods:A total of 408 consequent samples from eleven adults and five pediatric patients with SARS-CoV-2 infection were included. Reverse transcription-polymerase chain reaction (RT-PCR) and viral culture were performed for the samples obtained every other day from saliva, nasopharynx, feces, serum, urine, and tear. Anti-SARS-CoV-2 antib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, a recent meta-analysis showed that infectious potential declined after 9 days, even among patients with high viral loads in a respiratory specimen inferred from cycle threshold values. 68 69 In the present systematic review, virus isolation in saliva was attempted by nine studies, 15–23 but the presence of a typical cytopathic effect and detectable viral particles in the supernatant was reported by only four studies. 17–19 22 …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, a recent meta-analysis showed that infectious potential declined after 9 days, even among patients with high viral loads in a respiratory specimen inferred from cycle threshold values. 68 69 In the present systematic review, virus isolation in saliva was attempted by nine studies, 15–23 but the presence of a typical cytopathic effect and detectable viral particles in the supernatant was reported by only four studies. 17–19 22 …”
Section: Discussionmentioning
confidence: 88%
“…Virus isolation was attempted by nine studies15–23 and viral cultures were successfully performed in six,17–19 21–23 although the presence of typical cytopathic effect and or increased viral in the supernatant was reported in only four of them,17–19 22 with one of the studies showing that most patients shed live virus for ≥20 days 19…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations